TEACHING READING COMPREHENSION BY USING CONTENT-BASED INSTRUCTION (CBI) METHOD TO THE SECOND YEARS LEARNERS AT MTS AL-FURQON PRABUMULIH - Hedyan Putra; Lenny Marzulina (Edukasi, 2015)
The aims of this study were to find out; (1) Whether or not the implementation of Content-Based Instruction (CBI) method significantly improves reading comprehension to the second years learners at MTs. Al-Furqon Prabumulih, (2) The students’ opinions are toward the implementation of Content-Based Instruction (CBI) method in reading comprehension to the second years learners at MTs. Al-Furqon Prabumulih. Therefore, the main purpose of this study was designed to improve students’ reading comprehension using Content-Based Instruction (CBI) method. The investigation of population of this study was all the second years learners at MTs. Al-Furqon Prabumulih in the academic year 2013/2014, which consist of 63 students coming from two classes. The sample of this study were class II Pa consisting of 20 male students was treated as control group and class II Pi consisting of 20 female students was treated as experimental group, which selected using convenience sampling. In finding a significant improvement of students’ reading comprehension average score from pretest to posttest taught using Content-Based Instruction (CBI) method, the writer conducted ttest using Paired Sample t-test, it showed that the matched ttest calculation of specified α = 0.05 (95% level of significant) is 0.000 and degree of freedom (df) is 19, the t-value (tv) is 5.638 and the t-table (tt) is 1.729. It means that tv > tt (tvalue is higher than ttable). Consequently there was a significant progress from the scores of pretest to posttest since the t-value of matched t-test calculation is higher than t0.05, 19 = 1.729 and the level of significance is lower than α = 0.05. Meanwhile, in finding the students’ opinion toward the implementation of Content-Based Instruction (CBI) method, Percentage Formula is used to analyze the respondents’ answer on questionnaire constructed by the researcher. From the result of questionnaire analysis of this study, it can be stated that most of the students agreed that Content-Based Instruction (CBI) method improved their reading comprehension and it helped them to create interesting ways in learning English.